Application of approach for development of hptlc identification and quantification methods for determination of phenolic compounds and terpenoids of several thymus l. Species - Khokhlova, Kateryna; Vyshnevska, Liliia; Zdoryk, Oleksandr; Filatova, Olga (My University, 2021)
The aim of this work was to improve the approaches for standardization of Thymus L. species by development of HPTLC identification of phenolic compounds (flavonoids and phenylpropanoids) and terpenoids (essential oils and triterpenoids) and quantitative determination of rosmarinic acid and flavonoids for six Thymus L. species of Ukraine flora, as well as determination of chromatographic profiles of Thymus L. species’ extracts obtained using different extraction methods. Materials and methods. Objects were: samples of dry herb of Th.serpyllum, Th.vulgaris, Th.Marschallianus, Th.Pallasianus, Th.calcareus, and Th.moldavicus of Ukraine origin collected in 2019-2021 years or acquired commercially on Ukraine market. Instruments: CAMAG HPTLC Herbal System, visionCats 2.5. The analytical grade reagents were used. Reference substances were purchased from Extrasynthese, Sigma Aldrich. Chromatography was performed on HPTLC plates Si 60 F254, Merck according to the developed methods. Results. A new approach for quality control of different Thymus L. species of Ukraine flora included the development of HPTLC methods for identification of main groups of bioactive substances of these species, such as flavonoids and phenylpropanoids, essential oils, triterpenoids; development of quantification method of rosmarinic acid and assay of total flavonoids, expressed as luteolin-7-O-glucoside. The characteristic HPTLC fingerprints of six Thymus L. species in three mobile phases of different polarities that cover a wide range of bioactive substances were established. The content of rosmarinic acid in different Thymus L. species samples was in the range of 0,11-0,72 %: Th.moldavicus – 0,11 %; Th.Marschallianus – 0,19-0,27 %; Th.serpyllum – 0,38 %; Th.vulgaris – 0,51 %; Th.calcareus – 0,56 %; T.Pallasianus – 0,72 %. The total flavonoids content, expressed as luteolin-7-O-glucoside, was in the range of 0,8– 2,72 %: Th.moldavicus – 0,8 %; Th.serpyllum – 0,87 %; Th.vulgaris – 1,06 %; Th.Pallasianus – 1,28 %; Th.Marschallianus – 1,89 %; Th.calcareus – 2,72 %. Conclusions. The proposed scientific approach for quality evaluation of Thymus L. species using HPTLC allows to determine comprehensive information of chemical composition and content of active substances of multiple samples in parallel, in a cost and time-efficient manner
Application of approach for development of hptlc identification and quantification methods for determination of phenolic compounds and terpenoids of several thymus l. Species / K. Khokhlova, L. Vyshnevska, O. Zdoryk, O. Filatova // Science Rise: Pharmaceutical Science : scientific Journal, 2021. – № 4(32). – Р. 29–36.
Keywords: високоефективна тонкошарова хроматографія, тимус, стандартизація, ідентифікація, кількісне визначення, флавоноїди, ефірні олії, тритерпеноїди; high-performance thin-layer chromatography, Thymus, standardization, identification, quantification, flavonoids, essential oils, triterpenoids; высокоэффективная тонкослойная хроматография, тимус, стандартизация, идентификация, количественный анализ, флавоноиды, эфирные масла, тритерпеноиды